Arduino Uno Based Real Count Development as a Tool to Help Assessing Physical Exercise Results - Hartono, Adyan Argadhia; Sulaiman, Sulaiman; Rahayu, Setya (Journal of Physical Education and Sports, 2020)
The development of previous tools used by researchers to assess physical exercise results only uses one variable. For example, the assistive tool is only for the variables of push-up, sit-up, speed, agility, or reaction. In its development, researchers have created a tool using four variables, named Real Count. This type of development research is used to produce specific products and test the effectiveness of the product, research design, product needs analysis, initial product drafts, expert validation, improvement of initial product drafts, product effectiveness trials and small-scale trials, first product revisions and field trials, and revision of the final product. The instruments used to collect data were interviews, observations, questionnaires, and documentation. Data analysis techniques use a Likertscale of 1-5. The product effectiveness test is in the "excellent" category at assessing physical exercise. In the media expert product trials, stage 1 is in the "good" category, and stage 2 is in the "excellent" category. Phase 1 of the sports expert's product trial is in the "fair" category. Phase 2, small-scale product trials, and large-scale product trials are in the "excellent" category. This study concludes that Real Count has been created as a tool for assessing exercise in physical condition. The Real Count is feasible and effective to beused as a physical training tool in Pemalang Regency.